THE ROLE OF POSYANDU FOR THE ELDERLY IN IMPROVING THE HEALTH AND QUALITY OF LIFE OF THE ELDERLY: PERAN POSYANDU LANSIA DALAM MENINGKATKAN KESEHATAN DAN KUALITAS HIDUP LANSIA - Amarullah; Kusuma, Sony Aditya; Zuhryansah; Nurul Jariyatin; amar, sony (LPPM ISTeK ICsada Bojonegoro, 2025)
Posyandu for the elderly is one of the efforts to improve the health and welfare of the elderly in Indonesia. Services provided at Posyandu Lansia include routine health monitoring, disease prevention, and improving the quality of life of the elderly through social and psychological support. Posyandu Lansia is implemented in Rahayu Village to overcome health problems in the elderly. This Posyandu Lansia program is one of the collaborative programs between PT. Pertamini EP with ISTek ICSada Bojonegoro, where this program aims to improve the health welfare of the elderly. This study aims to explore the role of Posyandu Lansia in providing comprehensive health services and its contribution to improving the quality of life of the elderly. The method used in this study is a literature study. The results of the study indicate that Posyandu Lansia can increase the awareness of the elderly about the importance of a healthy lifestyle, reduce the prevalence of degenerative diseases, and detect early diseases in the elderly. The number of elderly who routinely participate in Posyandu activities is 45-50 elderly every month.